2012
DOI: 10.1161/strokeaha.111.634071
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life and Healthcare Resource Use Associated With Angiographic Vasospasm After Aneurysmal Subarachnoid Hemorrhage

Abstract: Background and Purpose— In this analysis of data from a large clinical trial in aneurysmal subarachnoid hemorrhage, the impact of angiographic vasospasm (aVSP) on specific patient outcomes and inpatient healthcare resource use was assessed. Methods— This was a post hoc analysis of exploratory end points collected for 409 patients with aneurysmal subarachnoid hemorrhage in the Clazosentan to Overcome Neurological Ischemia and Infarction Occurring After S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
47
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 33 publications
0
47
0
Order By: Relevance
“…This association supports the notion that vasospasm and cerebral ischemia are significant contributors to early and late SAH-related morbidity. 18,22,26,28,29,31,42,43 It also suggests that maneuvers to avoid cerebral ischemia during hospitalization are critical in optimizing the capacity for continued long-term clinical improvement.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…This association supports the notion that vasospasm and cerebral ischemia are significant contributors to early and late SAH-related morbidity. 18,22,26,28,29,31,42,43 It also suggests that maneuvers to avoid cerebral ischemia during hospitalization are critical in optimizing the capacity for continued long-term clinical improvement.…”
Section: Figmentioning
confidence: 99%
“…The pathogenesis of cerebral injury due to SAH is multifactorial and complex. Cerebral vasospasm, 18,31,42 hydrocephalus, 40 cortical spreading ischemia, 39 elevated intracranial pressure, 40 and cerebral metabolic dysfunction 34 have all been implicated in cerebral injury following aneurysm rupture. Our results suggest that in select patients, particularly younger patients with no radiographic evidence of large or eloquent stroke, the potential for delayed improvement is greatest.…”
Section: Figmentioning
confidence: 99%
“…20,25 Cerebral vasospasm is noted on angiography in as many as 70% of patients following aSAH and is predicted by high mean flow velocities (MFVs) on transcranial Doppler (TCD) ultrasonography. 19,24,26,35 Vasospasm is strongly associated with delayed cerebral ischemia (DCI) 12 and cerebral infarction, 11,39,49 although poor outcomes can still occur in its absence.…”
mentioning
confidence: 99%
“…8,38 Additionally, the severity of the initial hemorrhage was a powerful factor affecting clinical outcomes, presumably due to brain injury with nonischemic mechanisms. 6,31 Macdonald et al 29 showed that clazosentan reduced mortality and vasospasm-related morbidity in subgroup analyses in patients with a poor WFNS grade (≥ III) and diffuse thick SAH. However, the majority of eligible patients in pooled analysis had a WFNS grade of I or II, and it is possible that the effect of clazosentan may be more pronounced in patients with more serious SAH.…”
Section: 30mentioning
confidence: 99%
“…18,50 Specifically, clazosentan is an endothelin receptor antagonist under investigation for the prevention of vasospasm and vasospasm-related morbidity. 3,4,8,24,[27][28][29][30]37,40,42,43,[45][46][47] Recently, a series of well-designed clinical trials was performed using clazosentan in patients with SAH. In a Phase IIa trial, clazosentan reduced moderate or severe angiographic vasospasm by 55% relative to placebo (p = 0.008).…”
mentioning
confidence: 99%